Ibn Taymiyyah’s Views on Grammar: The Meaning of the Letter in Language and Terminology - habal, kairdin (El Omda in Linguistics and Discourse Analysis, 2018)
This article highlights certain grammatical aspects addressed by Shaykh al-Islam Ibn Taymiyyah in his book Majmū‘ al-Fatāwā, which clearly demonstrate his mastery of Arabic grammar. In this paper, I review Ibn Taymiyyah’s views on the meaning of the letter in the Arabic language and in the terminology of grammarians. Ibn Taymiyyah examines the opinions of grammarians on the matter, discusses them, and weighs their arguments, reflecting the depth of his grounding in Arabic grammar.